Odpowiedź :
Odpowiedź:
a)
P=UI | dzielimy obie strony przez I
U=P/I
P=UI | dzielimy obie strony przez U
I=P/U
b)
R=U/I | mnożymy obie strony razy I
U=RI
R=U/I | dzielimy obie strony przez U
I=R/U
Liczę na naj :D
Odpowiedź:
[tex]a)P=Ul[/tex]
[tex]P=Ul/:l[/tex]
[tex]U=\frac{P}{l}[/tex]
[tex]P=Ul[/tex]
[tex]P=Ul/:U[/tex]
[tex]l=\frac{P}{U}[/tex]
[tex]b)R=\frac{U}{l}[/tex]
[tex]R=\frac{U}{l}/*l[/tex]
[tex]U=Rl[/tex]
[tex]R=\frac{U}{l}[/tex]
[tex]R=\frac{U}{l}/*l[/tex]
[tex]Rl=U/:R[/tex]
[tex]l=\frac{U}{R}[/tex]
Szczegółowe wyjaśnienie: